2016
DOI: 10.1177/0009922816677038
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Trial of a Video Patient Decision Aid to Facilitate Early Intervention Referrals From Primary Care

Abstract: Many young children identified with developmental concerns in pediatric settings do not receive early intervention (EI). We assessed the impact of a video decision aid and text message reminder on knowledge and attitudes regarding developmental delay and EI as well as referral completion. We conducted a pilot randomized controlled trial in an urban setting and enrolled 64 parent-child dyads referred to EI. Compared with controls, participants who received the intervention demonstrated increased knowledge regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…20,21 A recent randomized trial assessing the impact of a 3-minute video decision aid on parents' attitudes regarding DD and appraisals of EI demonstrated favorable changes in these areas. 22 The third theme, it's not that I don't trust the doctor, appeared consistently across all stages of the help-seeking pathway. Mothers in our study (as with parents across cultures) 23, 24 relied on social networks for advice about their child's care and help-seeking behaviors.…”
Section: Theme 5: Limited and Conflicting Informationmentioning
confidence: 99%
“…20,21 A recent randomized trial assessing the impact of a 3-minute video decision aid on parents' attitudes regarding DD and appraisals of EI demonstrated favorable changes in these areas. 22 The third theme, it's not that I don't trust the doctor, appeared consistently across all stages of the help-seeking pathway. Mothers in our study (as with parents across cultures) 23, 24 relied on social networks for advice about their child's care and help-seeking behaviors.…”
Section: Theme 5: Limited and Conflicting Informationmentioning
confidence: 99%
“…32,33,36 Studies that conducted separate analyses explored the moderating effects of literacy or health literacy ( n = 5), education ( n = 8), numeracy ( n = 1), poverty or socioeconomic status (e.g., income, n = 2), ethnicity or race ( n = 5), geographical location ( n = 2), insurance status ( n = 3), or language preference ( n = 1) by including interactions in their analyses. One study that conducted a separate analysis restricted their analysis only within the low-literacy group but did not compare with a high-literacy group, 26 and another study conducted a separate analysis to test the effect of their intervention among Latino participants only. 22…”
Section: Resultsmentioning
confidence: 99%
“…45 Often, interventions included a combination of formats such as print/video ( n = 3). 21,38,40 Four studies used print/video with another element such as text messages, 26 telephone, 30,34 or face-to-face counseling. 42 It was generally not specified whether a modality was chosen specifically to accommodate users with low literacy, with the exception of 2 studies that reported using a touch-screen PtDA format to this end.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five PtDAs were included in the primary analysis. 3660 An additional 13 studies of SDM interventions were included in the secondary analysis (Figure 1). 6173…”
Section: Resultsmentioning
confidence: 99%